PROFILE OF JUNIOR HIGH SCHOOL STUDENTS’ CONCEPTUAL UNDERSTANDING OF VIBRATION, WAVES, AND LIGHT - Azhar Husnun Mawaddah (Jurnal Pembelajaran Sains, 2023)
This research aims to analyze the level of junior high school students' understanding of concepts related to vibration, waves, and light. The method used in this research is a mixed-methods approach, employing a sequential explanatory research design conducted at a state junior high school in Kamal sub-district. The population of this study includes all Grade VIII students during the odd semester of the 2023/2024 academic year. A purposive sampling technique was used to select a sample of 30 students. Data were collected using tests and interviews. The data collection involved a two-tier diagnostic test to assess students' conceptual understanding. The indicators used in this concept understanding test include explaining, classifying, interpreting, exemplifying, and concluding. Based on the research results, it can be concluded that: (1) students' overall conceptual understanding is moderate, (2) the two-tier diagnostic test results showed that the highest score was on the interpreting indicator, with 29%, and the lowest was on the classifying indicator, with 8%, (3) the analysis of student responses revealed that question number 4 had the highest percentage of correct answers at 80%, while question number 2 had the lowest percentage at 20%.